A Worldwide Tour of (Almost) Permaculture - Angela Gordon Glore (Journal of Agriculture, Food Systems, and Community Development, 2016)
First paragraphs: Sustainable [R]Evolution, edited by Juliana Birnbaum and Louis Fox, is a survey of permaculture (and permaculture-like) projects and communities throughout the world. Multiple authors have contributed short profiles of ecovillages, urban agriculture projects, farms, and teaching centers, interspersed with writings on permaculture design principles. Permaculture was coined—as a word and a design system—by Australians Bill Mollison and David Holmgren in the 1970s as a type of ecologically based permanent agriculture. Mollison's Permaculture: A Designer's Manual stands as the seminal work describing the elements of and values embedded in permaculture. It is an inherently personal form of gardening, tailored to a property's specific microclimates, topography, and use patterns....